Ehrlichia chaffeensis TRP32 Nucleomodulin Function and Localization Is Regulated by NEDD4L-Mediated Ubiquitination - Farris, Tierra R.; Zhu, Bing; Wang, Jennifer Y.; McBride, Jere W. (Frontiers in Cellular and Infection Microbiology, 2018)
Ehrlichia chaffeensis is an obligately intracellular bacterium that reprograms the mononuclear phagocyte through diverse effector-host interactions to modulate various host cell processes. In a previous study, we reported that the E. chaffeensis nucleomodulin TRP32 regulates transcription of host genes in several biologically relevant categories, including cell differentiation and proliferation. In this study, we investigate the effect of ubiquitination on TRP32 function and localization within the host cell. TRP32 is both mono- and polyubiquitinated on multiple lysine residues during infection and when ectopically expressed. Despite lacking a canonical PPxY motif, TRP32 interacted with, and was modified by the human HECT E3 ubiquitin (Ub) ligase NEDD4L. TRP32 ubiquitination was not by K48-linked polyUb chains, nor was it degraded by the proteasome; however, TRP32 was modified by K63-linked polyUb chains detected both in the cytosol and nucleus. HECT ligase inhibitor, heclin, altered the subnuclear localization of ectopically expressed TRP32 from a diffuse nuclear pattern to a lacy, punctate pattern with TRP32 distributed around the periphery of the nucleus and nucleoli. When a TRP32 lysine null (K-null) mutant was ectopically expressed, it exhibited a similar phenotype as single lysine mutants (K63R, K93R, and K123R). However, the K-null mutant showed increased amounts of cytoplasmic TRP32 compared to single lysine mutants or heclin-treated cells ectopically expressing TRP32. These alterations in localization corresponded to changes in TRP32 transcriptional repressor function with heclin-treated and single lysine mutants unable to repress transcription of a TRP32 target genes in a luciferase assay.